2012
DOI: 10.1159/000343273
|View full text |Cite
|
Sign up to set email alerts
|

RANTES Polymorphisms and the Risk of Graft-versus-Host Disease in Human Leukocyte Antigen-Matched Sibling Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: We investigated the association between RANTES (regulated upon activation, normal T cell expressed and secreted) polymorphisms and clinical outcomes in patients treated with allogeneic hematopoietic stem cell transplantation (allo-HSCT). Three RANTES gene polymorphisms, i.e. –403G/A (rs2107538), –28C/G (rs2280788) and In1.1T/C (rs2280789), were genotyped, and the effects of the genotypes and haplotypes of RANTES on clinical outcomes were analyzed. The competing risk regression analysis was used to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…Similar relationships were observed for recipients with AG haplotype [CCL5-403 (rs2107538)/CCL5-28 (rs1800825)]. On the other hand, Shin et al (2013), who analysed three CCL5 polymorphisms, -403G/A (rs2107538), -28C/G (rs2280788) and In1.1T/C (rs2280789), showed significant effects of the AGC haplotype on the cumulative risk of aGvHD and relapse-free survival.…”
Section: Ccl5supporting
confidence: 65%
“…Similar relationships were observed for recipients with AG haplotype [CCL5-403 (rs2107538)/CCL5-28 (rs1800825)]. On the other hand, Shin et al (2013), who analysed three CCL5 polymorphisms, -403G/A (rs2107538), -28C/G (rs2280788) and In1.1T/C (rs2280789), showed significant effects of the AGC haplotype on the cumulative risk of aGvHD and relapse-free survival.…”
Section: Ccl5supporting
confidence: 65%
“…Also in mice, anti-CD3 treatment during preconditioning reduced aGvHD by limiting both CCR7 + dendritic cells homing to lymph nodes and CCR9 + effector T cells homing to aGvHD target organs without reducing GvL [179]. In humans, both a CCL5 (RANTES; Regulated on Activation, Normal T Cell Expressed and Secreted) haplotype of three polymorphisms [180] and the expression of the CX3CL1/CX3CR1 pair [181] positively correlated with the occurrence of aGvHD. Depending on the cells bearing GPCRs, other chemokine receptors can prevent aGvHD.…”
Section: Resultsmentioning
confidence: 99%
“…Kim and colleagues showed that the CG genotype of rs2280788 in recipients of allo-HSCT was significantly associated with a higher incidence of chronic GVHD, extensive chronic GVHD, and severe grade of chronic GVHD compared to CC genotype [ 48 ]. In contrast, a study by Shin et al suggested that CCL5 variants may be associated with acute GVHD rather than chronic GVHD, as well as relapse-free survival in patients treated with allo-HSCT [ 49 ]. In the studies presented above, CCL5 polymorphisms have been rather negative prognostic factors of the risk of developing graft versus host disease.…”
Section: Discussionmentioning
confidence: 99%